A continuous flow reactor setup as a tool for rapid synthesis of micron sized NaA zeolite - Vandermeersch, Tobias; Van Assche, Tom R.C.; Denayer, Joeri F.M.; De Malsche, Wim (Microporous and mesoporous materials, 2016)
Slow crystallization kinetics and a limited thermodynamical stability of the target crystal phase are characteristic to zeolite formation, representing some of the key obstructions for fast zeolite synthesis. In this paper, the possibility of accelerating NaA zeolite synthesis in a continuous flow reactor (CFR) is studied. The CFR reduces the thermal lag by increasing surface to volume ratio, expediting heat transfer and mass transfer. The properties of the CFR and the reference batch synthesized particles were similar as confirmed by X-ray diffraction, scanning electron microscopy, particle size measurement using laser scattering and water adsorption equilibria. The reduced residence time and reduction in thermal lag provided an ideal synthesis environment for NaA zeolite, without side products, yielding 160 g/h per liter reactor volume of dry NaA crystals synthesized in 16 min and 2–3 μm particles for a single CFR. In comparison, the batch process produces 33 g/h per liter reactor volume The effects of diluting with NaOH-solution and temperature were studied in the CFR, allowing to determine the optimal conditions. With the enhanced reaction kinetics gained from the increased temperature and molar composition, NaA synthesis is performed 10 times faster than in the optimal batch synthesis. The optimal conditions for the synthesis of NaA in the CFR were determined as: a gel composition of Na2O:4.75 – SiO2:1.93 – Al2O3:1.0 – H2O:192, at a synthesis temperature of 150 °C during 16 min without, aging of the gel mixture. This paper shows that the bottlenecks in NaA zeolite synthesis can be widened resulting in faster synthesis in a CFR, making it a feasible pathway for more controllable zeolite synthesis at higher mass production rates (160 g/(h l-reactor)) while reducing the risk of blockage in a continuous flow reactor. [Display omitted] •A continuous flow reactor setup for controlled and rapid synthesis of meta stable products is proposed.•The setup was validated for 4A synthesis and illustrates the need for rapid temperature transfer rather than rapid heating.•Synthesis of micron sized 4A zeolite was achieved in 16 minutes.